'Chapter 7: Smartphone penetration test: Securing Industry 5.0 mobile applications' in "1st Edition, The Future of Human-Computer Integration Industry 5.0 Technology, Tools, and Algorithms". - Eka Wahyu, Aditya; Nur Haryani, Zakaria; Fazli, Azzali; Mohamad Nazim, Jambli (CRC Press, 2024)
The Future of Human-Computer Integration: Industry 5.0 Technology, Tools, and Algorithms provides a valuable insight into how Industry 5.0 technologies, tools, and algorithms can revolutionise industries and drive innovation.